PFAPA syndrome: a rare cause of periodic fever - Kurtaran, Hanifi; Karadağ, Ahmet; Çatal, Ferhat; Aktaş, Davut (The Turkish Journal of Pediatrics, 2004)
PFAPA syndrome (periodic fever, aphthous stomatitis, pharyngitis, adenopathy) is characterized by abrupt onset of fever, malaise, aphthous stomatitis, tonsillitis, pharyngitis and cervical adenopathy. The age of onset of the disease is four years, with a range of 6 months to 7 years. The syndrome is sporadic and nonhereditary. Long-term sequelae do not develop. A nine- year-old boy presented with sore throat, fever and oral aphthae. After taking a throat culture, he was prescribed oral antipyretic and was called for a follow-up visit the next day. As the culture result was negative, he was given a single dose prednisolone with the suspected diagnosis of PFAPA. Twenty-four hours later his temperature was 36.8 degrees C, with all his complaints regressed. Twenty-two days later the patient was again admitted to our hospital with the same complaints. Again, single dose oral prednisolone was given after a throat culture. On the next day the patient was free of all symptoms and the culture was again normal. To our knowledge this is the first PFAPA case report from Turkey in the literature.